The Influence of Emotional Intelligence and School Principal Leadership on Teacher Work Behavior - Ramlah Ramlah; Sukirman Nurdjan; Hilal Mahmud (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This research aims to determine the influence of emotional intelligence and school principal leadership on teacher work behavior at the Public Senior High Schools (SMA) in Palopo. This research employs a quantitative approach with an ex-post facto causal design, involving 77 teachers from the Public Senior High Schools in Palopo as the research sample. Data analysis is conducted using multiple linear regression analysis with the assistance of SPSS, including partial t-tests and simultaneous F-tests. When considered simultaneously, the research findings indicate that emotional intelligence and school principal leadership significantly affect teacher work behavior, with a significance value of 0.002 < 0.005 and a determination coefficient of 45.4%. These results suggest that as the level of emotional intelligence and the effectiveness of school principal leadership increase, so does the quality of teacher work behavior in fulfilling their duties and responsibilities as educators. The implications of this research reveal that one of the contributing factors to the quality of teacher work behavior is the emotional intelligence of the school principal, coupled with their leadership, which influences teachers to exhibit positive work behavior.